Tolerance between religions through the role of local wisdom and religious moderation - Pajarianto, Hadi (HTS teologiese studies, 2022)
Religion and culture play a central role in building harmonious relations between followers of different religions, both within the nuclear family and in the extended family. This study examines the revitalisation of religious moderation with a cultural approach in strengthening tolerance. Data was obtained qualitatively from in-depth interviews and observations of families of different religions, religious leaders, traditional leaders, and other relevant informants. The research findings show that the family institution is the most crucial place in carrying out moderate religious culturalisation through the local wisdom values of kasiuluran [kinship], tengko situru [togetherness], and karapasan [tenacity]. Institutionally, traditional leaders, religious leaders, and clans in Tongkonan encourage peace in society, both in traditional and religious activities. Meanwhile, religious celebrations, traditional ceremonies, and community activities are occasions to socialise and interact by placing a firm tolerance for religious differences.Contribution: This study contributes to the realisation of tolerance through the application of moderate religious values and local wisdom that the world needs today. Strengthening inter-religious relations is very important because the position of religion is complex and sensitive. This contribution is crucial in the midst of the rampant issue of radicalism in Indonesia lately.